Correlating self- and transport diffusion in the Knudsen regime - Bunde, Armin; Kärger, Jörg; Russ, Stefanie; Zschiegner, Stephan (Diffusion Fundamentals, 2005)
Comparing the rates of molecular diffusion in porous materials under different regimes of measurement may provide valuable information about the underlying mechanisms. After quite generally explaining the benefit of such a procedure, we refer to a case which in the last few years has raised controversial discussion within the community, viz. the comparison of diffusion phenomena in pores of varying roughness in the so-called Knudsen regime. Knudsen diffusion represents the limiting case of molecular diffusion in pores, where mutual encounters of the molecules within the free pore space may be neglected and the time of flight between subsequent collisions with the pore walls significantly exceeds the interaction time between the pore wall and the molecules. In our studies, the coefficients of self- and transport diffusion are found to be in satisfactory agreement, which contradicts previous literature data. A number of effects which might becloud this relationship are discussed.